Analyzing causality and cointegration of macroeconomics and energy-related factors of Nordic and SEE European countries - Georgescu, Irina Alexandra; Oprea, Simona-Vasilica; Bâra, Adela (Journal of Business Economics and Management, 2024)
Discrepancies between several South-Eastern European (SEE) countries and Nordic countries are investigated in this paper using an econometric analysis. Its aim is to examine the relationship between CO2 emissions, GDP per capita, urban population (URB) and electricity production from Renewable Energy Sources (RES) – EPREN, excluding hydroelectric for the two groups of EU countries located in the North and S-E of Europe. The data covers a period from 1990 to 2022, providing a comprehensive view over three decades. The relationship between the four variables is determined by various causality and cointegration tests. We check the unit root tests and conclude that the analyzed time series are stationary at first difference. Further, we estimate two models: Fully Modified and Dynamic Ordinary Least Squares and study causality and cointegration between variables. The results show that CO2 emissions are impacted by GDP, URB and EPREN for both regions. Testing causality, for SEE and Nordic countries, the bidirectional and causalities do exist.